Biodefence and the production of knowledge: rethinking the problem. Issue 4 (22nd December 2011) - Buchanan, Allen; Kelley, Maureen C
Abstract : Biodefence, broadly understood as efforts to prevent or mitigate the damage of a bioterrorist attack, raises a number of ethical issues, from the allocation of scarce biomedical research and public health funds, to the use of coercion in quarantine and other containment measures in the event of an outbreak. In response to the US bioterrorist attacks following September 11, significant US policy decisions were made to spur scientific enquiry in the name of biodefence. These decisions led to a number of critical institutional changes within the US federal government agencies governing scientific research. Subsequent science policy discussions have focused largely on 'the dual use problem': how to preserve the openness of scientific research while preventing research undertaken for the prevention or mitigation of biological threats from third parties. We join others in shifting the ethical debate over biodefence away from a simple framing of the problem as one of dual use, by demonstrating how a dual use framing distorts the debate about bioterrorism and truncates discussion of the moral issues. We offer an alternative framing rooted in social epistemology and institutional design theory, arguing that the ethical and policy debates regarding 'dual use' biomedical research ought to be reframed as a larger optimisation problem across a plurality of values including, among others: (1) the production of scientific knowledge; (2) the protection of human and animal subjects; (3) the promotion and protection of public health (national and global); (4) freedom of scientific enquiry; and (5) the constraint of government power.